Analysis of Misconceptions with the CRI (certainty of response index) Method on Organ System Materials for Enrichment of Biology Teaching Materials - Sri Maryanti; Sri Hartati; Nisa Sholehah Pangsuma (Jurnal Report of Biological Education, 2023)
Individual ability to understand what is taught is the first step to improve students' cognitive learning outcomes. However, often students are not able to understand existing concepts, misinterpret concepts, or concepts received are not in accordance with the concepts of experts. This research is a descriptive research with a survey method. This study aims to determine the percentage of students who master the concept, do not know the concept, experience misconceptions (misconceptions) and lucky guesses (lucky guesses) and analyze the level of student understanding of the material on organ systems. The sub-matter included is the reproductive system, digestive system, respiratory system, and excretory system. The benefits of this research can also be recommended in compiling appropriate learning materials so that misunderstandings can be minimized. The population in this study were 25 basic biology education students. The instrument used is a multiple choice question consisting of 50 questions on organ system material equipped with a Certainty of Response Index (CRI) value on a scale of 0-5. The instruments used were interview sheets and true-false choice tests along with the reasons accompanied by. Based on the research data obtained, it can be described that the average respondent has a misconception of 48% as indicated by the number of respondents who answered incorrectly with high CRI criteria. Almost every sub-chapter of material on organ systems has misconceptions. Misconceptions about the hormonal system accounted for the largest percentage of the total percentage of misconceptions. This is indicated by the average misconception in the material of 14 out of the total. Based on these findings it can be used as an evaluation to create learning tools that will be implemented through learning in general biology courses. Key Words: CRI, Misconception, Teaching material